ETR 300 : Nursery Plantation / Azalina Abdullah ...[et al.] - Abdullah, Azalina; Asmuni, Nor 'Azizi; Mohamad Hanif, Shabnam Haseena; Yahaya, Sariza; Mohamad, Norhayati (2000)
Green Peace Nursery develops this business plan and it will be operate starting from January 2001. Green Peace Nursery is a business, which is base on concept of proposed young plant and productive oil palm trees. The certified clones of seed are purchased from reputable breeders such as FELDA, PORIM and GUTHRIE and we will grow them until the maturity age that is 7 month. The type of clones that we only focus is DxP or Tenera. DxP is the best type of palm oil. It comes from consolidation of palm oil that is Dura and Pisifera. Tenera or DxP produce more oil and more heavy than other types. Each 'tandan' of Tenera or DxP will produce 23.7 % of oil and the heavy is 58.4 kg.